Xylan degradation improved by a combination of monolithic columns bearing immobilized recombinant β‐xylosidase from Aspergillus awamori X‐100 and Grindamyl H121 β‐xylanase. Issue 1 (15th December 2014) - Volokitina, Maria V.; Bobrov, Kirill S.; Piens, Kathleen; Eneyskaya, Elena V.; Tennikova, Tatiana B.; Vlakh, Evgenia G.; Kulminskaya, Anna A.
Abstract Synergistic action of exo‐ and endohydrolazes is preferred for effective destruction of biopolymers. The main purpose of the present work was to develop an efficient tool for degradation of xylan. Macroporous lab‐made monolithic columns and commercial CIM‐Epoxy disk were used to immobilize the recombinant β‐xylosidase from Aspergillus awamori and Grindamyl β‐xylanase. The efficiency of xylan degradation using the low‐loaded β‐xylosidase column appeared to be four times higher than for the in‐solution process and about six times higher than for the high‐loaded bioreactor. Disk bioreactor with the Grindamil β‐xylanase operated in a recirculation mode has shown noticeable advantages over the column design. Additionally, a system comprised of two immobilized enzyme reactors (IMERs) was tested to accelerate the biopolymer hydrolysis, yielding total xylan conversion into xylose within 20 min. Fast online monitoring HPLC procedure was developed where an analytical DEAE CIM disk was added to the two‐enzyme system in a conjoint mode. A loss of activity of immobilized enzymes did not exceed 7% after 5 months of the bioreactor usage. We can therefore conclude that the bioreactors developed exhibit high efficiency and remarkable long‐term stability.